Drug-resistant malaria: molecular mechanisms and implications for public health - Petersen, Ines; Eastman, Richard; Lanzer, Michael (FEBS letters, 2011)
Resistance to antimalarial drugs has often threatened malaria elimination efforts and historically has led to the short-term resurgence of malaria incidences and deaths. With concentrated malaria eradication efforts currently underway, monitoring drug resistance in clinical settings complemented by in vitro drug susceptibility assays and analysis of resistance markers, becomes critical to the implementation of an effective antimalarial drug policy. Understanding of the factors, which lead to the development and spread of drug resistance, is necessary to design optimal prevention and treatment strategies. This review attempts to summarize the unique factors presented by malarial parasites that lead to the emergence and spread of drug resistance, and gives an overview of known resistance mechanisms to currently used antimalarial drugs.